ChemInform Abstract: 2, 4‐Bis(4‐aryl‐1, 2, 3‐triazol‐1‐yl)pyrrolo[2, 3‐d]pyrimidines: Synthesis and Tuning of Optical Properties by Polar Substituents. Issue 36 (September 2015) - Bucevicius, Jonas; Skardziute, Lina; Dodonova, Jelena; Kazlauskas, Karolis; Bagdziunas, Gintautas; Jursenas, Saulius; Tumkevicius, Sigitas
Abstract Novel D‐π‐A‐π‐D type chromophores, the title pyrimidines (III), synthesized by Cu(I)‐catalyzed Huisgen azide‐alkyne cycloaddition reaction of 2, 4‐diazidopyrimidines (I) with ethynylarenes (II).